Agricultural adaptation of strawberry farmers to extreme weather occurrences a case study - Andrada, Erika Mae P.; Navarro, Jenica M. (2011)
This study looks at the adaptation strategies employed by strawberry farmers in La Trinidad, Benguet as a response to extreme weather occurrences by means of describing the farmers' cropping practices such as crop mix, crop rotation, tillage practices, and the use of alternative crops. Strawberry production levels were also obtained and were analysed using regression analysis i order to create a trend. It was found out that strawberry farmers actually employ adaptation strategies to cope with climate change. It was also found out in the regression analysis that strawberry production levels in La Trinidad increases over time even alongside with extreme weather occurrences -- Author's abstract.
Thesis (Bachelor of Science in Biology)--University of the Philippines Baguio, 2011.
Includes bibliographical references (leaves 57-60)
Keywords: Agricultural systems -- Philippines -- La Trinidad (Benguet)